Vitamin D genes influence MS relapses in children. (July 2020) - Graves, Jennifer S; Barcellos, Lisa F; Krupp, Lauren; Belman, Anita; Shao, Xiaorong; Quach, Hong; Hart, Janace; Chitnis, Tanuja; Weinstock-Guttman, Bianca; Aaen, Gregory; Benson, Leslie; Gorman, Mark; et al.
Objective: The aim of this study was to determine whether a vitamin D genetic risk score (vitDGRS) is associated with 25-hydroxyvitamin D (25(OH)D) level and multiple sclerosis (MS) relapses in children. Methods: DNA samples were typed for single nucleotide polymorphisms (SNPs) from four genes previously identified to be associated with 25(OH)D levels. SNPs with strong associations with 25(OH)D after multiple comparison correction were used to create a genetic risk score (vitDGRS). Cox regression models tested associations of vitDGRS with relapse hazard. Results: Two independent SNPs within or near GC and NADSYN1/DHCR7 genes were strongly associated with 25(OH)D levels in the discovery cohort ( n  = 182) after Bonferroni correction. The vitDGRS of these SNPs explained 4.5% of the variance of 25(OH)D level after adjustment for genetic ancestry. Having the highest versus lowest vitDGRS was associated with 11 ng/mL lower 25(OH)D level (95% confidence interval (CI) = −17.5, −4.5, p  = 0.001) in the discovery cohort. Adjusting for ancestry, sex, disease-modifying therapy (DMT), and HLA-DRB1*15 carrier status, the highest versus lowest vitDGRS was associated with 2.6-fold (95% CI = 1.37, 5.03, p  = 0.004) and 2.0-fold (95% CI = 0.75, 5.20, p  = 0.16) higher relapse hazard in the discovery and replication cohorts, respectively. Conclusion: The vitDGRS identifies children at greater risk of relapse. These findings support a causal role for vitamin D in MS course.